"Non-invasive" portable laser ablation sampling of art and archaeological materials with subsequent Sr–Nd isotope analysis by TIMS using 1013 Ω amplifiers. Issue 11 (20th September 2017) - Knaf, A. C. S.; Koornneef, J. M.; Davies, G. R.
Abstract : A new integrated trace element and multi-isotope provenancing methodology is presented that uses a portable "non-invasive" pulsed laser ablation sampling device. Abstract : A new integrated trace element and multi-isotope provenancing methodology is presented that uses a portable "non-invasive" pulsed laser ablation sampling technique. Samples are collected on location onto Teflon filters for return to a clean laboratory for low blank (pg) geochemical procedures. Ablation pits approximately 60 or 120 μm in width and depth remove μg amounts of material. Following dissolution, trace element ratios are determined by inductively coupled plasma mass spectrometry and combined Sr–Nd isotopes by thermal ionization mass spectrometry. Use of 10 13 Ω resistors allows precise analysis of subnanogram amounts of Sr–Nd isotopes, which coupled with the trace element data, provides highly effective multi-variant discrimination for material provenance and authenticity verification. Monitoring of blank contributions is required.